Synergy Sense – Kinetic (SMC) Using(VTSS.S) and Its Relationship to The accuracy of The Landslide and Straight Punching Performance in Volleyball - Dr. Jinan Naji Zwayen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research included the introduction and the importance of the research, as the researcher touched on the role of sensory-motor coordination (SMC) using (VTSS.S), an important role in mastering and developing basic skills in many sports and sports events, including volleyball, which is one of these important processes that work On the success of the application of various skills, it also helps to develop quick solutions for individual and group skills. The skill of crushing beating is one of the skills that require compatibility between hands, eyes and feet. The importance of the research came through emphasizing the role of sensory-motor compatibility exercises (SMC) for the purpose of teaching and developing them in a good and correct manner using the Vienna System (VTSS.S) with the aim of developing the accuracy of performing some diagonal and straight smash hits. The aim of the research is to identify the relationship between sensory-motor compatibility (SMC) and concentration of attention and the accuracy of the high crushing method (diagonal and rectilinear), and the research community consisted of students of the fourth stage in the College of Physical Education - University of Baghdad, whose number is (229) students. The researcher conducted a lottery process to select (40) students randomly. The high smash hit test, the sensorymotor compatibility test (SMC) and the numbered circuit test were conducted in the indoor hall of the volleyball court at the College of Physical Education, and the researcher reached several results, including: The researcher reached recommendations, including emphasizing the use of synergy-sense-kinesthetic exercises (SMC), in terms of the Vienna system, because it helps in developing the compatibility of the eye, hand and leg to develop the sensekinesthetic synergy (SMC) for students of the Faculty of Physical Education. The researcher recommended several recommendations to emphasize the use of Sense-Motor Synergy (SMC) exercises, in terms of the Vienna System, because it helps in developing the compatibility of the eye, hand and leg to develop Sense-kinesthetic synergy (SMC) for students of the Faculty of Physical Education.